PERAN SUPERVISOR DALAM MENINGKATKAN KUALITAS LEMBAGA PENDIDIKAN ISLAM: SYSTEMATIC LITERATURE REVIEW - Qomariya Rahma Ayu; Nurul Muayyadah; Abdurrozaq Abdurrozaq; Mardiyah Mardiyah; Mukhlishah Mukhlishah (Jurnal Manajemen Pendidikan, 2026)
The role of supervisors in improving the quality of Islamic educational institutions has become increasingly strategic amid demands for adaptive and sustainable improvements in educational quality. This study aims to analyze the roles, responsibilities, and competencies of supervisors in supporting the improvement of educational quality. The study employs a Systematic Literature Review (SLR) approach by examining various scientific literature from 2021 to 2026 through the stages of identification, selection, and analysis based on the PRISMA guidelines. The results indicate that supervisors serve as monitors, mentors, facilitators, and quality drivers through academic and managerial supervision. However, a gap was identified between the ideal concept of supervision and field practices, characterized by planning that is not data-driven, implementation that lacks collaboration, evaluation that is not evidence-based, and weak follow-up on supervision. Supervisors’ competencies, encompassing professional, pedagogical, and managerial aspects, are key factors in determining the effectiveness of supervision. This study emphasizes that strengthening supervisors’ competencies and developing an adaptive, data-driven, and sustainable supervision system are essential for comprehensively improving the quality of Islamic educational institutions.